Tricuspid transcatheter valve-in-valve: an alternative for high-risk patients - Gaia, Diego Felipe [UNIFESP] (2012)
Tricuspid valve disease is not uncommon. Some patients with tricuspid valve disease require tricuspid replacement with bioprosthesis and, over time, may require re-interventions. Transcatheter tricuspid valve-in-valve approach has emerged as an alternative to treat dysfunctional bioprosthesis. in this article, we report a case of a patient with four previous cardiac interventions presenting with tricuspid bioprosthesis dysfunction. the patient was treated with the transcatheter transatrial tricuspid valve-in-valve procedure. the procedure was successful with no residual leakage and a non-significant mean gradient. the patient recovered well and was discharged in 1 week. the procedure is a feasible alternative for high-risk patients. Selection and postoperative care are crucial for the outcome.